PENGUKURAN PENDAYAGUNAAN DANA ZAKAT PRODUKTIF DALAM UPAYA PENGENTASAN KEMISKINAN BERDASARKAN CIBEST MODEL (Studi Kasus BAZNAS Kabupaten Banjar) - Mahyuni; Havivah, Nur (P3M Politeknik Negeri Banjarmasin, 2022)
Zakat is a part of Islamic teachings that plays an important role in reducing poverty. Productive zakat is believed to be able to improve the welfare of the community in a sustainable manner with the concept of utilization through various programs, such as business capital assistance. The purpose of this study is to prove whether the productive zakat utilization program is effective in reducing poverty using the CIBEST Model analysis. Respondents were determined using purposive sampling technique with 20 mustahik respondents of BAZNAS Banjar Regency. The conclusion is that productive zakat assistance is effective in reducing the poverty level of mustahik. The welfare index (Quadrant I) increased by 0.1 (10%), the material poverty index (Quadrant II) decreased by 0.1 (10%), while the spiritual poverty index (Quadrant III) and absolute poverty index (Quadrant IV) did not change with a value of 0 (0%).